Developing a cellular manufacturing model considering the alternative routes, tool assignment, and machine reliability - Sayyed Mahdi Sadat Khorasgani; Mahdi Ghaffari (Journal of Industrial Engineering International, 2018)
The cell formation (CF) is one of the most important steps in the design of a cellular manufacturing system (CMS), which it includes machines' grouping in cells and part grouping as separate families, so that the costs are minimized. The various aspects of the problem should be considered in a CF. The machine reliability and the tool assigned to them are the most important problems which have to be modeled correctly. Another important aspect in CMS is material handling costs that they consist of inter-cell and intra-cell movement costs. Moreover, setup and tool replacement costs can be effective in CF decision making. It is obvious that CF cannot be completed without considering the number of demand. With considering of all of the above aspects, an extended linear integer programming is represented for solving the cell formation problem (CFP) in this study. The objective is to minimize the sum of inter-cell movement, intra-cell movement, tool replacement, machine breakdown, and setup costs. In the other terms, for states that cost of movement is higher than tool-changing cost, although a part can have the inter- and/or intra-cell movements, the model tries to find a solution which part is allocated to one cell and with changing the tools, processes of that part is completed. In addition, to validate the model and show its efficiency and performance, several examples are solved by branch and bound (B&B) method.
Keywords: 650; Cell formation problem; Material handling costs; Alternative processing routes; Tool assignment; Machine reliability; Branch and bound